COMPARISON OF HUMAN PAPILLOMAVIRUS 16 EXPRESSION BY IMMUNOHISTOCHEMISTRY IN CERVICAL CARCINOMAS AND NON-NEOPLASTIC CERVICAL MUCOSA - Yousuf, Sarah; Rauf, Fozia; Danyal; Ahmareen Khalid Sheikh (Journal of Postgraduate Medical Institute, 2022)
Objective: To compare the prevalence of Human Papillomavirus 16 in cervical carcinoma and non-neoplastic cervical mucosa by immunohistochemistry. Methodology: From September 2020 to November 2021, this retrospective cross-sectional study was conducted at the Department of Pathology, Peshawar Medical College, Riphah International University Islamabad, Pakistan. On FFPE blocks of 38 cervical carcinoma cases and 38 non-neoplastic cervical mucosa by immunohistochemistry using a monoclonal antibody against HPV 16 by Bio-SB. SPSS 20 was used for the analysis of data. Results: The mean age of cervical carcinoma patients was 55.18 ± 11.536. The majority of the Cervical carcinoma cases were more than 50 years of age (n= 28, 73.6%). HPV16 positivity was observed in 44.7 % cases of cervical carcinoma and 5.35 % of normal cervical mucosa. The p-value was < 0.00007 and hence statistically significant. HPV 16 expression was higher in the patients with cervical carcinoma in the fourth and fifth decade of life. Among the subtypes of cervical carcinoma, 60.5 % (n=23/38) were Squamous cell carcinoma out of which 43.5% (n=10/23) were positive for HPV 16 expression, Adenocarcinoma subtype was 34.2% (n=13/38) out of which 46.2% (n=6/13) were positive and the Adenosquamous subtype was 5.3% (n=2/38) out of these 1 was positive for HPV 16 expression. High grade tumors (n=18) showed higher HPV 16 expression (61.1%) as compared to low grade lesions (30.0%). Conclusion: HPV 16 expression is higher in cervical carcinoma cases as compared to normal cervical mucosa. Although not statistically significant high-grade tumors showed higher expression of HPV 16.